Anterior Interosseous Nerve Neuropraxia Secondary to Shoulder Arthroscopy and Open Subpectoral Long Head Biceps Tenodesis. (16th April 2017) - Steed, Jeremiah T.; Drexler, Kathlyn; Wooldridge, Adam N.; Ferguson, Matthew
Abstract : Arthroscopic rotator cuff tendon repair is a common elective procedure performed by trained orthopaedic surgeons with a relatively low complication rate. Specifically, isolated neuropraxia of the anterior interosseous nerve (AIN) is a very rare complication of shoulder arthroscopy. An analysis of peer-reviewed published literature revealed only three articles reporting a total of seven cases that describe this specific complication following standard shoulder arthroscopic procedures. This article reports on three patients diagnosed with AIN neuropraxia following routine shoulder arthroscopy done by a single surgeon within a three-year period. All three patients also underwent open biceps tenodesis immediately following completion of the arthroscopic procedures. The exact causal mechanism of AIN neuropraxia following shoulder arthroscopy with biceps tenodesis is not known. This case report reviews possible mechanisms with emphasis on specific factors that make a traction injury the most likely etiology in these cases. We critically analyze our operating room setup and patient positioning practices in light of the existing biomechanical and cadaveric research to propose changes to our standard practices that may help to reduce the incidence of this specific postoperative complication in patients undergoing elective shoulder arthroscopy with biceps tenodesis.